Changing social and political attitudes in Ireland and Northern Ireland - James Laurence; Stefanie Sprong; Frances McGinnity; Helen Russell; Garance Hingre (The Economic and Social Research Institute (ESRI), 2023)
The 21st century has seen significant social, political, and economic change on the island of Ireland. This report draws on multiple sources of high-quality, comparative social survey data to explore the development of social and political attitudes in Ireland, North and South, over the past 25 years. In Ireland, attitudes are tracked from 1998 to 2023. In Northern Ireland, more limited survey data sources mean most attitudes are tracked from 1998 to 2018 only. This is the first study to compare and contrast trends in attitudes on the island of Ireland over the past two decades. In doing so, the report provides insight into how social and political attitudes have changed over the last 25 years ('overall trends'); whether different social groups are experiencing different trends in attitudes (especially those who finished education earlier or later); whether there are generational differences in attitudes, and how these are changing over time. This analysis can help policymakers and civil society understand what conditions lead to positive societal attitudes and perceptions of fairness, political efficacy, and trust.
Keywords: 330; Politische Einstellung; Öffentliche Meinung; Irland